Meningkatkan Hasil Belajar Ipa Di Kelas IV SD Negeri Poboya Melalui Metode Inkuiri - Takulo, Megawati; Surahman, Surahman; Rizal, Rizal; Pahriadi, Pahriadi (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2024)
The main problem in this study was the low science learning outcomes of fourth-grade students at SD Negeri Poboya. The initial results indicated that most students had not yet achieved the minimum mastery criteria, either individually or classically. This situation required the use of a more effective learning strategy to improve students’ understanding. Therefore, this study applied the inquiry method, which emphasizes active student involvement in observing phenomena, discovering concepts, and drawing conclusions based on their own learning experiences. The research employed Classroom Action Research conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The findings revealed that the inquiry method significantly improved students’ science learning outcomes. In the first cycle, the classical mastery level was only 63% with an absorption rate of 64.21%. After improvements in the second cycle, classical mastery increased to 100% with an absorption rate of 88.42%. These results demonstrate that the inquiry method not only enhanced learning outcomes but also created a more interactive, enjoyable, and motivating learning atmosphere, encouraging students to actively engage in understanding science concepts.